An assessment of land degradation and alien plants invasion in the Waterberg Biosphere Reserve, Limpopo Province - Mokubedi, Lucia Macheba (Department of Environmental and Geographical Science, 2022)
Land degradation and invasion by alien plants are interconnecting issues that span both natural and socio-economic systems. As a result, addressing the complexity and severity of these pressures requires the use of a multidisciplinary approach. This study aims to assess land degradation and invasive alien plants distribution and their impacts on the ecosystem services within the WBR. An area outside the reserve was designated as a control to compare how degradation processes have evolved over the last few decades. Landsat images captured in 1989, 2000, 2013, and 2017 were used to analyse and map the land use/cover change. The images were classified into the following classes: water bodies, woody vegetation, grasslands, cultivated fields, bare lands, and settlements. Change detection performed between the years showed that the area outside the WBR has been losing grasslands and woody vegetation and gained more bare lands, cultivated fields, and settlements. On the contrary, the area within the WBR lost a significant amount of bare land and gained grasslands, woody vegetation, and a small amount of cultivated fields and settlements. The roadside survey was used to assess the distribution of invasive alien plants along the main roads in the selected areas. A single observer drive-by method was used to record the alien plants present at an interval of 5 km. To understand how the communities are being influenced by land degradation and alien plants invasion, focus group discussions were held to understand how their livelihoods are affected. Four important indicators, namely vegetation loss, land-use intensity, alien plants distribution, and population pressure, were overlaid using ArcMap 10.1 to determine the land degradation severity in both study areas. The results revealed that land degradation was severe outside the WBR, where most human activities occur, regardless of population pressure and alien plant distribution. These issues were intensifying with profound, severe implications for people's livelihoods, as land is the leading resource from which communities, both within and outside the WBR, eke their living. The WBR experienced land recovery following the proclamation of the area as a formal biosphere reserve by UNESCO, which has constrained the harmful impact of human activities. Reversing degradation and invasion by alien plant species requires sustainable land use and planning based on the current land-use practices and landscape attributes. Therefore, integrating local and scientific knowledge is helpful in the planning of sustainable and efficient land management.